Effects of chest and limb physiotherapy along with mindfulness meditation, in promoting early discharge from the ICU, in a patient with intermediate syndrome: a case study - Satra, Dhruvi M.; Kulkarni, Madhur S. (International Journal of Research in Medical Sciences, 2025)
Organophosphorus (OP) poisoning is a critical public health concern, particularly in developing countries like India, where it can lead to life-threatening complications. A major consequence of OP poisoning is Intermediate Syndrome (IMS), characterized by respiratory and proximal limb muscle weakness, often progressing to respiratory failure. Timely initiation of ventilatory support is crucial, as delays can be fatal. IMS patients frequently require prolonged ICU stays and mechanical ventilation, which may result in secondary complications such as Deep Vein Thrombosis (DVT), limb edema, atelectasis from pulmonary secretions, and ICU-acquired weakness. Prolonged ICU stays can also lead to significant anxiety and agitation in patients, making weaning from mechanical ventilation challenging due to persistent respiratory muscle weakness. This study evaluated the effectiveness of a combined physiotherapy and mindfulness-based intervention in promoting early ICU discharge in a 36-year-old male farmer diagnosed with OP poisoning and IMS, following ingestion of Tafgor under alcohol influence. The patient was intubated and placed on a ventilator. A one-week protocol was implemented, including chest physiotherapy, limb physiotherapy, and mindfulness meditation. Pre- and post-intervention assessments were conducted using the Chelsea Critical Care Physical Assessment Tool, Richmond Agitation-Sedation Scale, and ventilator weaning status. The results demonstrated significant improvement in physical and psychological parameters, with better ventilator weaning and reduced ICU stay. The study concluded that integrating physiotherapy and mindfulness practices can play a pivotal role in accelerating recovery and promoting early ICU discharge in patients with IMS secondary to OP poisoning.